Estados Unidos y el proceso de transnacionalización en la postguerra - Bouzas, Roberto (Estudios Internacionales, 1984)
During the 25 years that followed the end of World War II, the advanced capitalist countries went through a period of unprecedented economic expansion that culminated, in the early 1970s, in a prolonged economic crisis. Throughout this period of sustained growth, there was a process of transnationalization and growing inter-capitalist ties. In this work three themes are developed: First, the evolution of the transnationalization process in the postwar period is reviewed, concentrating the analysis on the dynamics of the United States economy. A second section discusses some of the elements of transnationalization that, in the current situation, represent sources of conflict either for the North American economy or for the administration of international order. Third, a close reflection is made about the three most articulated attempts to respond to the disorder of the seventies.